Dialectal Variations In The Egyptian Edraak Media Video Podcast: A Dialectological Study - Jambak, Mellinda Raswari; Muasssomah; Abdul Basid (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2025)
Dialectal variations reflect the richness of culture and the identity of communities, particularly in Arabic, which encompasses a wide range of dialects. This study focuses on the phonological and morphological variations in the Egyptian Amiyah dialect as used in the Edraak Media podcast, specifically the episode